Pengaruh Kesadaran Wajib Pajak, Kepemilikan Nomor Pokok Wajib Pajak, dan Sanksi Pajak terhadap Kepatuhan Wajib Pajak Orang Pribadi - Condro Widodo; Raphita Celyna A.A. Tambunan; Sri Trisnaningsih (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
This study aimed to determine the effect of taxpayer awareness, ownership of a taxpayer identification number, and tax sanctions on individual taxpayer compliance (Case Study at KPP Pratama Surabaya Rungkut). The type of method used is quantitative. The population in this study is all individual taxpayers registered at KPP Pratama Surabaya Rungkut. The number of samples used in this study are 100 respondents who are calculated based on the slovin formula with the sampling technique that is incidental sampling. Data collection techniques in this study are carried out using the questionnaire method on the Google form. The data analysis technique used in this study is Structural Equation Modeling (SEM) using SmartPLS 3.2.9 for data management. The results of this study indicate that: (1) Taxpayer awareness has no effect on individual taxpayer compliance at KPP Pratama Surabaya Rungkut. (2) Ownership of a taxpayer identification number affects individual taxpayer compliance at KPP Pratama Surabaya Rungkut. (3) Tax sanctions have no effect on individual taxpayer compliance at KPP Pratama Surabaya Rungkut Keywords: Taxpayer Awareness; Ownership of Taxpayer Identification Number; Tax Sanctions; Taxpayer Compliance